Viscum Album—Magical Plant of Complexity and Paradox - Cicchetti, Jane Tara (Homœopathic Links, 2015)
This article covers the history of Viscum album as a homeopathic remedy from 1850 up to the present day, as well as the use of mistletoe in traditional herbalism. The natural history of the plant and its folklore are discussed. Its contemporary use as a cancer remedy in anthroposophic medicine for the treatment of cancer is explained as well as Rudolf Steiner's theory of etiology of cancer and why he chose mistletoe as a primary treatment for that disease. There is a final discussion on recent dream provings of the remedy.
Keywords: Viscum album; Rudolf Steiner; Mistletoe therapy; Anthroposophic medicine; Cancer; Metamorphosis; Druids; Dreams